The intensity of the magnetic field on different sex of fetus and accuracy of sex detection using gold ring pendulum - Anwar, Mawakia; Samsudewa, Daud; Muhlisin, Zainul; Endrosuseno, Jatmiko (Livestock and Animal Research, 2023)
Objective: This research aims to measure the intensity of magnetic field of different sex of fetuses and the accuracy of pendulum method for the sex detection of cow fetuses.Methods: Twenty-six Madura cows with gestational age of more than 4 months were used in this research. This research is composed of three steps : 1). Measuring the intensity of the magnetic field on the fetus using an Electromagnetic Field Meter (EMF) type 827 which is affixed to the right side of the abdomen 2). Observe the pattern of the gold ring pendulum used for sex detection of cow fetus 3). Measure the accuracy of the pendulum ring gold method. The data were analyzed using descriptive analysis.Results: The result of this research showed that the intensity of the magnetic field of a male fetus is 0.04 µT for a head, 0.07 µT for back, 0.05 µT for abdomen and 0.03 µT for tail. Magnetic field of a female fetus is 0.03 µT for head, 0.05 µT for back, 0.035 µT for abdomen and 0.01 µT for tail. The gold ring pendulum is a unidirectional pattern for detection male sex showed the accuracy of 91.67% and a rotating pattern for female fetuses showed accuracy of 85.71%. The average accuracy of detection using the gold ring pendulum is 88.46%.Conclusions: The conclusion of this research is male fetuses have a magnetic field higher than male fetus.